Social media engagement among young Malaysian teenagers and its relationship with academic achievement - Nurul Syazwani Elias (Kulliyah of Education, International Islamic University Malaysia, 2020)
The prevalence and importance of social media as a medium of communication, education and entertainment has raised concerns regarding their high usage and engagement among Malaysians, especially among school-aged students. Given the concerns, this study explores and profiles the social media engagement of young Malaysian teenagers and its association with their academic achievement. In addition, the study attempts to uncover significant differences, if any, among urban, suburban and rural secondary school students in engagement and academic achievement. The study adopts the ex-post facto survey research design with data collected from 451 young Malaysian teenagers aged between thirteen to seventeen years old using stratified and simple random sampling. Among the results are that most Malaysian teenagers use social media, particularly WhatsApp, YouTube and Instagram, between one and six hours daily at all times throughout the week, especially before going to bed. Despite their frequent engagement, the teenagers do not perceive their social media use to have a negative impact on their academic and social activities. Pointing likely to a digital divide, urban and suburban teenagers engage significantly more in social media than their rural counterparts. However, a weak negative correlation characterizes the relationship between social media engagement and academic achievement, suggesting that increased engagement in these media is associated with decreased test scores and academic performance. Considering teenagers' attachment to and fondness of social media, the study recommends that teachers use these media for learning purposes and activities to reap optimum benefits from them.